Optical properties of the CaEuAl3O7 phosphor with dual‐activator Eu2+/Eu3+ for multifunctional applications. Issue 10 (6th July 2020) - Xu, Yang; Sun, Zhen; Wei, Yanling; Jia, Mochen; Hou, Bofei; Li, Xin; Lin, Fang; Zhang, Mingxuan; Wang, Huayao; Fu, Zuoling
Abstract: At present, most blue‐red composite LED light sources are widely used in the field of plant lighting. However, their full‐width at half‐maximum of blue light is too small to meet the requirements of plants for photosynthesis. Herein, a dual‐emitting single‐phase self‐luminescent phosphor CaEuAl3 O7 (CEAO) is reported in this study, which provides broadband blue emission of Eu 2+ ions and red emissions of Eu 3+ ions. According to the optical properties of Eu 2+ and Eu 3+ ions in the CEAO phosphor, it can be found that all emissions are consistent with the absorption of chlorophylls and pigment carotenoids. In addition, the temperature sensing based on the fluorescence intensity ratio (FIR) in the CEAO phosphor is also studied and the maximum sensitivity ( S ) can reach as high as 6.90% K −1 at 313 K. The results indicate that the single‐component phosphor CEAO with blue and red double‐color emission possesses an outstanding potential in plant growth lamps and optical thermometry applications. Abstract : Multifunctional CaEuAl3 O7 (CEAO) phosphor provides a much blue broader emission of Eu 2+ and a series of red emissions of Eu 3+ ions, it can be observed that all emissions match well with the absorption of chlorophylls and pigment carotenoids, which can be combined with the near‐ultraviolet LED chip to realize the application of plant growth lights. In addition, based on the temperature‐dependent intensity ratio from the Eu 2+ ions (5 d ‐4 f ) and the Eu 3+ ions ( 5 D 0 ‐ 7 F 2, 4 ), the maximum sensitivity ( S ) of emission spectrum can be as high as 6.90% K −1 at 313 K, endowing CaEuAl3 O7 to have superior performance in temperature sensing.